Implementation of Quizizz Educational Game Media in Increasing Students’ Learning Motivation During the Covid-19 Pandemic in Islamic Religious Education Learning - Anggi Asmara Firdaus; Imam Tabroni; Irma Megawati (Journal of Social Transformation and Regional Development, 2022)
This study aims to explain and describe how the implementation of learning using the Quizizz educational game media in increasing students’ learning motivation during the Covid-19 pandemic in learning Islamic religious education. In this study the authors used a qualitative approach, the data sources were obtained from interviews, observations and documentation to teachers and students of SMAN 1 Campaka class X MIPA 1 and 2. The theoretical analysis used was Leony about learning media with Quizizz and Sardiman AM theory for analysis. motivation to learn.Based on data analysis, it can be concluded that: (1)The implementation of the Quizizz educational game media is well implemented, creating effective and fun learning and responding to the challenges of teachers in the very rapid development of the times and the emergence of the Covid-19 pandemic which requires learning to be carried out remotely, the impact of using Quizizz is to increase learning motivation, learning that attracts students’ enthusiasm and interest in learning, a busy but still conducive learning environment (2) Supporting factors for the application of Quizizz media are the availability of facilities in the form of projectors, loudspeakers, electrical connecting cables, wifi in every class, while the inhibiting factor is the internet network which is less strong and stable (3) the results of the learning evaluation show a very good score, the highest score is 100% and the lowest score is 53%.